A Survey and Analysis of the Impact of Cultural Hegemony in Film and Television Drama Works on Chinese Audiences - Meng XiaoYuan (Foundations and Trends in Modern Learning, 2026)
This study explores the cultural impacts of overseas film and television drama works on Chinese audiences and their perceptions of cultural hegemony. It conducts an in-depth analysis of the degree of cultural integration of overseas film and television dramas among Chinese audiences. The results show that contemporary Chinese audiences do not simply equate the dissemination of overseas film and television dramas with cultural hegemony, but hold an objective attitude of being open and inclusive while regarding such impacts as a balance of advantages and disadvantages. This reflects that against the backdrop of cultural confidence construction, audiences have formed a natural cultural barrier. The research conclusions provide empirical support for domestic film and television dramas to enhance their competitiveness and express cultural confidence in the context of globalization.